Migrasi Masyarakat Batak Toba Dan Relevansinya Terhadap Kemajuan Sumber Daya Manusia Di Kawasan Danau Toba : Migrasi Masyarakat Batak Toba Dan Relevansinya Terhadap Kemajuan Sumber Daya Manusia Di Kawasan Danau Toba - Harisan Boni Firmando (Jurnal Sosiologi Nusantara, 2024)
The Batak Toba community has migrated to various regions, and many of them lack an understanding of the background behind this migration, resulting in decreasing attention towards their hometown. The aim of this research is to analyze the migration of the Batak Toba community and the relevance of this migration to the advancement of human resources, which includes migration as a means of actualizing life goals and the advancement of human resources in the Lake Toba area. To analyze this social phenomenon, a qualitative method is used in this research. The findings of the study indicate that migration is a social action of the Batak Toba community to meet their needs, and this action is based on cultural values, namely the life goals of the community which serve as motivation for their behavior. The dispersion of the Batak Toba community to various regions is a social capital that can advance human resources in the Lake Toba area. In order for the efforts to advance human resources to be realized, the Batak Toba community who have migrated to various regions need to educate their families in the villages, such as through assistance in agriculture and small and medium enterprises that are community-based.